Consequences of pH change on wastewater depth filtration using a multimedia filter. (1st January 2018) - Ncube, Philani; Pidou, Marc; Stephenson, Tom; Jefferson, Bruce; Jarvis, Peter
Abstract: Different media materials in a multimedia filter have the potential to trap particles of different characteristics dependent on the media-suspension particle interactions. However, the removal of particles from wastewater secondary effluent using granular media filtration is relatively poorly understood because of the complexity of the wastewater matrix. Often the wastewater treatment process is liable to undergo pH changes due to removal or addition of chemicals in the treatment chain or from biological instability which in turn may alter the wastewater characteristics. Wastewater contains a mixture of organic and inorganic components, dissolved or particulate which may influence the aggregation and deposition of suspension solids during depth filtration. Changes in wastewater pH has the potential to change the wastewater matrix and media surface properties hence affecting aggregation and deposition in wastewater filtration. This study investigated how pH change affects wastewater filtration by monitoring zeta potential, aggregation and deposition of solids. The wastewater and filter media were also characterised over a range of pH from 1 to 13. Aggregation and deposition of wastewater solids was found to be most efficient near neutral pH. This was not concurrent with the conditions of lowest net charge in the system. Graphical abstract: Image 1 Highlights: Multimedia filtration of wastewater is more significantly impacted by pH than charge. The surface charge of the media in the filter rapidly matches that of the wastewater. DLVO interactions do not accurately describe particles aggregation in wastewater. Long range interactions contribute to particles aggregation and capture in the filter. Solids capture occurred through the entire depth of the multimedia filter bed.